(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
Historians’ interest in objects has grown over time, intersecting with studies on consumption, fashion, and economic value. This contribution explores the circulation of objects as commodities in the late Middle Ages, analyzing written and material sources to understand the dynamics of production, commercialization, and consumption. The volume focuses on the transformation of objects into marketable goods, highlighting the shift from self-production to mass purchasing. The individuality of objects emerges through their social and economic perception, with distinctive features such as origin, material, and use. Particular attention is given to medieval customs registers, which provide detailed insights into the classification and taxation of goods. At the same time, medieval archaeology offers crucial data on the dissemination of ceramic and metal artifacts, revealing the progressive expansion of markets. This volume presents an interdisciplinary analysis, linking history and economics to outline the commercial expansion and globalization of late medieval consumption. It highlights how the increasing availability of objects marked a profound social transformation, foreshadowing the modern culture of consumption.